DAMRI BUS PERFORMANCE IN PALANGKA RAYA CITY WITH IMPORTANCE PERFORMANCE ANALYSIS METHOD - Nova E. Sitopu; Tarita Aprilani Sitinjak; Lola Cassiophea (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2022)
One of the keys to the success of urban transportation is the quality of public transport services. One of the public transportation available in Palangka Raya City is the Damri bus. However, the quality of Damri bus service is still not optimal. To find out the level of performance of the Damri bus service, a poll is needed on the level of service, especially from the Damri bus users. This research was conducted to measure the performance level of Damri buses in the city of Palangka Raya. The method used in this research is distributing questionnaires. Data analysis used quadrant analysis with the Importance Performance Analysis (IPA) method. The results of data analysis show that the performance of Damri bus services is quite good, there are ten attributes that are in quadrant II (maintain achievement), namely service at ticket sales counters served quickly and regularly, Damri bus officers dress neatly and cleanly, there is evidence of retribution , passengers arrive at their destination, officers are responsible for passenger baggage, officers are willing to serve and prioritize passenger needs, officers do not look at social status and treat passengers with respect, officers are honest and patient in providing services, schedule information is available, continued Damri bus routes, and seats available enough and good . However, there are still 2 attributes that need improvement in calculating performance levels with interest/hope, namely drivers who drive according to the rules and the Damri bus fleet in good condition, clean and usable.